If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7n + -9 = 2n + 16 Reorder the terms: -9 + 7n = 2n + 16 Reorder the terms: -9 + 7n = 16 + 2n Solving -9 + 7n = 16 + 2n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-2n' to each side of the equation. -9 + 7n + -2n = 16 + 2n + -2n Combine like terms: 7n + -2n = 5n -9 + 5n = 16 + 2n + -2n Combine like terms: 2n + -2n = 0 -9 + 5n = 16 + 0 -9 + 5n = 16 Add '9' to each side of the equation. -9 + 9 + 5n = 16 + 9 Combine like terms: -9 + 9 = 0 0 + 5n = 16 + 9 5n = 16 + 9 Combine like terms: 16 + 9 = 25 5n = 25 Divide each side by '5'. n = 5 Simplifying n = 5
| 6(n+3)=0 | | (r-2)(r+10)=9 | | 2x-13=x+41 | | -4(4n+2)=20 | | 8-4x=15-5x | | 3(3g+40)-9g-120=0 | | 2x-40=x-20 | | 0.8x-0.3(50+x)=0.2(50) | | (x-2y)dx+(2x+y)dy=0de | | y=2x^2+kx+4 | | Q=60-4Pforp | | 5t^2+4t=0 | | 5=-3n+4n | | 3x+8=12X | | 9=3x-8 | | S=7x^2y | | h+(2h-1000)=440 | | c/12=5 | | z+4=69 | | 24x^3-15x^2+8x-5= | | 4z-2-(1-z)=4 | | 3+9(x-4)=8-8(x-7) | | =(4x+3)(4x-3) | | (-5a^3b^3)(6ab^5)= | | 13-x=209 | | a-17=18 | | x+(2x+1000)=4400 | | 3(3k+5)-14k+8+5= | | 3x+17-x+17=-4 | | 10k+73=2(5k+34) | | x=2x^2-6 | | b=a+8 |